A Study on the Optimal Number of Mobile Carriers: Discussion of Discussion of Magic Number – three or four - Masashi Ueda (International Telecommunications Society (ITS), 2021)
In recent years, mergers between communications companies have been progressing especially in mobile carriers' market. Regulatory authorities are worried about increasing consolidations and less competition, and have decided to impose conditions on the mergers or even disapprove them. In many cases, just before the generation change, the competitively inferior operators sell their business and exit the market because of the cost of acquiring spectrum. The concern of the regulators is cases such as Ireland and Austria, where ARPU rose because the competitive environment became milder due to mergers between MNOs. On the other hand, in Germany, where measures to promote competition after the merger (reallocating part of the new company's spectrum to other companies, leasing out 20% to 30% of its capacity, etc.) were effective, ARPU did not increase. On the other hand, when a window for new spectrum acquisition opens, new entrants may join the market. In the fifth generation (5G), Dish in the US, 1&1 Drillisch in Germany, and Rakuten in Japan took advantage of the opportunity to enter the market. In the case of Drillisch and Rakuten, they acquired spectrum and/or licenses in 2019 with the expectation of migrating existing customers from MVNOs to MNOs. (...)
Keywords: 330